2017
DOI: 10.1177/2472630317703982
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Microscale Technique for Determining the Erythrocyte Sedimentation Rate

Abstract: The erythrocyte sedimentation rate (ESR) is a commonly used test to screen for inflammatory conditions such as infections, autoimmune diseases, and cancers. However, it is a bulk macroscale test that requires a relatively large blood sample and takes a long time to run. Moreover, it provides no information regarding cell sizes or interactions, which can be highly variable. To overcome these drawbacks, we developed a microfluidic microscopy-based protocol to dynamically track settling red blood cells (RBCs) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The ESR is calculated based on the changes in the optical signals and results also show a very high correlation coefficient of about R 2 = 0.86 [218]. Furthermore, a vertical microfluidic system embedded with a cell-tracking system has been implemented for imaging to provide an edge over conventional analysis by reducing the sample volume and the analysis time [219]. RBCs also can form face-to-face branched or linear structures under static conditions or low-shear rates in the presence of appropriate macromolecules and are termed as 'rouleaux.'…”
Section: Analysis Of Rbcs Sedimentation Using Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESR is calculated based on the changes in the optical signals and results also show a very high correlation coefficient of about R 2 = 0.86 [218]. Furthermore, a vertical microfluidic system embedded with a cell-tracking system has been implemented for imaging to provide an edge over conventional analysis by reducing the sample volume and the analysis time [219]. RBCs also can form face-to-face branched or linear structures under static conditions or low-shear rates in the presence of appropriate macromolecules and are termed as 'rouleaux.'…”
Section: Analysis Of Rbcs Sedimentation Using Microfluidicsmentioning
confidence: 99%
“…Figure 12 shows an optofluidic point-of-care device for quantitative investigation of erythrocyte aggregation during coagulation with the schematics [221]. Another example for determining the erythrocyte sedimentation rate has enabled research of settling RBCs in terms of the diameter of cells and the population of cell/rouleau of different sizes [219]. Furthermore, the idea of combining the benefits of laser aggregometry, flow cytometry, and optical tweezers has been successfully implemented for the assessment of fibrinogen macromolecules interaction with RBC membranes [222].…”
Section: Analysis Of Rbcs Sedimentation Using Microfluidicsmentioning
confidence: 99%
“…In previous studies, a driving blood syringe was set in the vertical direction (i.e., upright or inverted). In addition, the hematocrit was set to relatively lower levels than the normal level of 45% (i.e., 0.1% [17], 20% [11], 25% [30], and 30% [21,31]). The hematocrit of the blood tended to increase over time when the blood was supplied from the bottom region of the syringe into the microfluidic device.…”
Section: Contributions Of Rbc Sedimentation For Control Bloodmentioning
confidence: 99%
“…A previous method has been employed to detect differences in the ESR between control blood and periodontitis blood [5]. Seelamantula et al have suggested a hybrid imaging technique for computing the setting velocity of an individual RBC in a vertical microfluidic channel [17]. Elbuken et al have proposed a portable microfluidic opto-electro-mechanical system [18].…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40] Blood plasma is then separated from blood aer a certain duration. Aer injecting small amounts of blood (75 mL, 41 40-200 mL 41 ) into a microuidic chamber, quantitative information of RBC sedimentation is obtained by measuring microscopic images, 42 optically transmitted light, 41,43 and blood conductivity 28 or electrochemical impedance. 44 In contrast, when blood samples are supplied to a microuidic device from a driving syringe pump, RBC sedimentation occurs continuously.…”
Section: Introductionmentioning
confidence: 99%